PENGARUH RHODAMINE B PERORAL DOSIS BERTINGKAT SELAMA 12 MINGGU TERHADAP GAMBARAN HISTOPATOLOGIS JANTUNG TIKUS WISTAR - Bayu Arif Wibowo; Saebani Saebani (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Rhodamine B dye is available in the market for the textile industry. This substance is often misused as a food coloring and cosmetics in many countries. This substance is most dangerous when consumed can cause disturbances in the function of organs, in the long term could be carcinogenic. This study aims to prove the existence of a relationship with a rhodamine-dose cardiac muscle cell damage Objective.Objective : To ascertain the differences of the images of cardiac histopathology caused by administration of Rhodamine B peroral with graded doses in 12 weeks.Methods : This research is True experimental laboratoric using post test only control group as it’s design. Sample of this research are 30 male wistar rat that fulfill the criteria for inclusion and exclusion, then divided randomly using simple random sampling. Rhodamine B consumption is 0 mg/kg BW in control group; 1/16 lethal dose (55,44 mg/kg BW) in treatment group I; 1/8 lethal dose (110,88 mg/kg BW) in treatment group II; 1/4 lethal dose (221,75 mg/kg BW) in treatment group III; 1/2 lethal dose (443,5 mg/kg BW) in treatment group IV; lethal dose (887 mg/kg BW) in treatment group V. Data collection is done with direct observation of images of spleen histopathology. Hypothesis testing using one-way Anova test continued with Post Hoc test.Result : There is an increase area of fibrosis in treatment 1, treatment 2, treatment 3, treatmen 4. Highest increasement on fibrosis area is found in traetment 4Conclusion : The myocardial has increased by time to time development, especially significant at group 4